Insect biomass is not a consistent proxy for biodiversity metrics in wild bees. (February 2021) - Vereecken, Nicolas J.; Weekers, Timothy; Leclercq, Nicolas; De Greef, Stéphane; Hainaut, Hélène; Molenberg, Jean-Marc; Martin, Youri; Janssens, Xavier; Noël, Grégoire; Pauly, Alain; Roberts, Stuart P.M.; Marshall, Leon
Highlights: Insect biomass alone cannot predict biodiversity metrics across contrasting habitats. Biodiversity metrics other than biomass or insect abundance should be mainstreamed. Patterns of phylogenetic diversity (PD) are consistent using different trees. Species identification is key for conservation tailored to the targeted organisms. Abstract: Recent studies have reported on dramatic cases of aerial insect population declines by focusing on the measure of the total biomass of caught insects. However, there is currently no consensus about how biomass patterns among sites and habitats might consistently capture the subtleties of changes in aerial insect community structure. Here, we investigated the relationship between the total biomass of wild bees collected using pan traps in urban, agricultural, and semi-natural habitats on one hand, and a spectrum of biodiversity metrics on the other hand, particularly species richness (SR), alpha diversity, functional diversity (FD) and three different forms of phylogenetic diversity (PD). Our results indicate that although biomass is significantly and highly correlated with the abundance of wild bees, it is generally significantly but only moderately and non-linearly correlated to the various facets of wild bee diversity among habitats. By contrast, we also found that all three measures of PD used are consistent across habitats, suggesting that a taxonomic hierarchy based on Linnaean classification could be used as a proxy for the measurement of PD in wild bees, particularly in other well-studied areas such as Western Europe where a multi-gene molecular phylogeny is unavailable as yet. Collectively, our results illustrate the clear limitations of biodiversity monitoring through measures of trapped insects biomass. We advocate for more robust measures of biodiversity trends in wild bees, requiring both standardized surveys, and the identification of caught specimens down to the species level to capture the subtleties of species, traits-based and phylogeny-based community changes across habitats or time. Scaling out this approach is an essential prerequisite for more global conservation planning tailored to the ecological requirements of the targeted insect species.